Design of Portable Sinks With Foot Pedal Valves For Prevention of Virus Spread in Medan Selayang District - Hasugian, Ivo Andika; Sitorus, Erwin; Bukit, Ferry Rahmat; Hasibuan, Novrida (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
At the beginning of 2020, the world was shocked by the outbreak of a new virus, namely a new type of coronavirus (SARS-CoV-2) and the disease is called Coronavirus disease 2019 (COVID-19). Until now this virus is rapidly spreading and research is still ongoing. One of the basic prevention efforts of the corona virus or Covid-19 is to diligently wash hands in detail and thoroughly. This is because the corona virus is transmitted through droplets or body fluids that come out when coughing or sneezing. Alfurqon Mosque is one of the places of worship in Medan Selayang District which is a red zone area. It is said to be a red zone because these are areas where residents are positively infected with Covid-19. Based on data from the Medan city health office in April 2020 in this region there were 10 positive patients in treatment. The Alfurqon Mosque has a congregation registered with the STM (Union Please Help) as many as 600 heads of families. So far, this mosque has not provided a place for washing hands specifically accompanied by soap / hand soap. The solution offered is to provide appropriate technology in the form of a hand washing sink that has a 520 liter water tank integrated with a water source pipes and has two sinks accompanied by liquid soap in each sink. This tool uses a foot pedal-style tap valve to turn on and close the water tap so that after washing the hands of the congregation there is no need to touch the tap again.